Pengaruh Konformitas Remaja dengan Teman Sebaya terhadap Perilaku Membolos di MTS Al-Mubarak Marisa - Muh Wahyuddin S. Adam; Pratiwi Samad; Nurain Pakaya; Alya Rahma; Megawati Hapulu; Yoanna Grace Fun (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
The aim of this research is to assess the influence of adolescent conformity on truant behavior at MTS Al-Mubarak Marisa. To collect data in research using case study techniques, students, guidance and counseling teachers, and homeroom teachers were observed and interviewed. These findings indicate that the main element influencing students' actual behavior is peer social pressure. Internal considerations are another component that influences actual behavior.